Preliminary refinement of rotation parameters of asteroids based on photogrammetric processing of on-orbit remote sensing images - Z. Peng; Z. Peng; X. Geng; X. Geng; J. Zhang; J. Zhang; Y. Wang; Y. Wang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
In recent years, asteroid exploration has become an important research direction in the field of deep space exploration. The weak gravitational environment of asteroids, as well as their complex topographic, geomorphic, and dynamic characteristics, pose significant technical challenges to surface exploration. The determination of high-precision asteroid rotation parameters is a fundamental requirement for engineering implementation and scientific research in deep space exploration missions. These parameters provide key information for establishing the asteroid coordinate system, which supports the transformation between the inertial frame and the body-fixed frame. Although traditional ground-based observation methods (such as light curve inversion) can provide preliminary estimates of rotation parameters, their accuracy is insufficient to meet the requirements of high-resolution remote sensing mapping and 3D reconstruction. Therefore, developing refinement methods for rotation parameters based on on-orbit remote sensing images has become a key technical approach. This paper proposes a preliminary refinement method for asteroid rotation parameters based on minimizing the residuals of forward intersection. First, rigorous geometric model incorporating the right ascension and declination is constructed, and the rotation parameters are gradually optimized through a "brute-force" search strategy. Experiments using on-orbit remote sensing images of Ceres, Vesta, and Ryugu asteroids verify the robustness and feasibility of the proposed method. The experimental results show that the proposed method can effectively refine the rotation parameters and remain stable even in the presence of initial orbit-determination errors.